Melatonin Suppresses NLRP3 Inflammasome Activation via TLR4/NF-κB and P2X7R Signaling in High-Fat Diet-Induced Murine NASH Model - Saha M; Manna K; Das Saha K (Dove Medical Press, 2022)
Moumita Saha,1 Krishnendu Manna,2 Krishna Das Saha1 1Cancer Biology and Inflammatory Disorder Division, CSIR-Indian Institute of Chemical Biology, Kolkata, West Bengal, India; 2Department of Food and Nutrition, University of Kalyani, Kalyani, West Bengal, IndiaCorrespondence: Krishna Das Saha, Cancer Biology and Inflammatory Disorder Division, CSIR-Indian Institute of Chemical Biology, 4 Raja S.C. Mullick Road, Kolkata, West Bengal, 700032, India, Tel +91 33 2499 5810, Fax +91 33 2473 5197, Email krishna@iicb.res.inBackground: NLRP3 inflammasome activation plays a critical role in mediating inflammation and NASH (non-alcoholic steatohepatitis) progression that ultimately leads to cirrhosis and hepatocellular carcinoma. Melatonin (MLT) controls high-fat diet-induced NASH in the murine model by modulating NLRP3 mediated inflammation. P2X7R-mediated inflammasome activation is reported in several inflammatory models including NASH.Objective: The role of MLT in P2X7R-mediated inflammation in the NASH model has not yet been explored. The present study investigated the role of MLT in amending high-fat diet-induced nonalcoholic steatohepatitis in the murine liver.Methods: To evaluate the hepatological changes, mice were divided into four groups to investigate the improvement potential of this MLT (10 and 20 mg/kg) and to assess the experimental findings. Histology, biochemical assays, ELISA, FACS analysis, Western blotting, and IF were performed to assess the physical and molecular changes upon melatonin treatment.Results: The result demonstrated that MLT administration reduced HFD (high-fat diet)-induced non-alcoholic steatohepatitic indices, which successively restored the hepatic morphological architecture and other pathophysiological features too. Moreover, the application of MLT suppressed HFD-induced activation of the inflammasome and through TLR4/NF-κB signaling. Herein, we report that MLT significantly suppresses P2X7R expression and calcium influx along with inflammasome in both in vitro and in vivo. The docking study revealed a strong binding affinity of MLT with P2X7R. Moreover, the results also showed that the Nrf2 level was boosted which may normalize the expression of antioxidant proteins that safeguard against oxidative damage triggered by inflammation. Furthermore, some matrix metalloproteinases like MMP 2 and MMP 9 were repressed and TIMP-1 level was increased, which also signifies that MLT could improve liver fibrosis in this model.Conclusion: Based on our findings, this study may conclude that MLT could be used as a therapeutic agent in the high-fat diet-induced NASH model as it has persuasive anti-inflammatory potential.Graphical Abstract: Keywords: melatonin, NASH, NAFLD, inflammasome, P2X7, inflammation, Kupffer cells